On New χ-Fixed Point Results for λ−Υ,χ-Contractions in Complete Metric Spaces with Applications - Babak Mohammadi; Wutiphol Sintunavarat; Vahid Parvaneh (Journal of Mathematics)
The main aim of this work is to introduce the new concept of λ−Υ,χ-contraction self-mappings and prove the existence of χ-fixed points for such mappings in metric spaces. Our results generalize and improve some results in existing literature. Moreover, some fixed point results in partial metric spaces can be derived from our χ-fixed points results. Finally, the existence of solutions of nonlinear integral equations is investigated via the theoretical results in this work.